Evaluation of calcium release and pH value of light-cured cavity liners for pulp-capping materials - Kamila de Figueiredo PEREIRA; Rosymere Freitas de Sousa CRUVINEL; Andrea Abi Rached DANTAS; Milton Carlos KUGA (Universidade Estadual Paulista, 2018)
Abstract Introduction Cavity liners based calcium hydroxide present low strength and high solubility that is consider a disadvantage. In order to enhance these properties it was developed a light-cured cavity liner based calcium hydroxide containing resin. Objective The purpose of this study was to evaluate the pH and calcium release of light-cured cavity liners. Material and method There were prepared specimens (n=10) with the Ultra-Blend ® plus, Biocal® (light cured cements) and Hydro C® (control). The samples were stored in 10 mL of distilled water and maintained at 37 °C. After 24 hours, 7, and 14 days, there were analyzed pH and the release of calcium levels. The data were statistically analyzed by ANOVA and Tukey test (α = 0.05). Result The results of pH showed Hydro C > Ultra-Blend plus > Biocal. Biocal presented worst calcium release. Conclusion Light-cured materials present lower calcium release and alteration in pH values.